2019
DOI: 10.1111/1467-8500.12374
|View full text |Cite
|
Sign up to set email alerts
|

Why do “teeth” need “voice”? The case of anti‐corruption agencies in three Australian states

Abstract: Interactions between horizontal accountability agencies (e.g., anti‐corruption agencies [ACAs]) and social accountability actors (e.g., journalists, civil society activists, and complainants/whistleblowers) are recognized as important to horizontal agencies’ performance, but the reason(s) is not clear. This study therefore explores why horizontal accountability agencies need social accountability actors in performing their functions. The study analyses data from 30 key stakeholders in Australia, including ACAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Social accountability could generate “spilling out” effects to traditional forms of accountability and such increasing its indirect but substantial influence over public sector actions and behaviors (Neu et al, 2020, p. 474). Social accountability could function as a “trigger” for forms of accountability, such as parliamentary questioning (political accountability) and inspections (judicial accountability; see, for example, Ankamah, 2019; Ojala et al, 2019; Reichersdorfer et al, 2013). Whether social accountability occurs in a consensual or confrontational nature might have consequences for formal and vertical accountability.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social accountability could generate “spilling out” effects to traditional forms of accountability and such increasing its indirect but substantial influence over public sector actions and behaviors (Neu et al, 2020, p. 474). Social accountability could function as a “trigger” for forms of accountability, such as parliamentary questioning (political accountability) and inspections (judicial accountability; see, for example, Ankamah, 2019; Ojala et al, 2019; Reichersdorfer et al, 2013). Whether social accountability occurs in a consensual or confrontational nature might have consequences for formal and vertical accountability.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Furthermore, the “weak” mechanisms of social accountability could result into formal sanctions, as these accountability mechanisms are often connected with traditional accountability arrangements toward hierarchical powers (Schillemans, 2008, p. 191). For example, Ankamah (2019) shows that societal stakeholders have a strong supportive role for the effective performance of accountability functions by anti-corruption agencies in three Australian states. Based upon a multiple case study of accountability in immigration administration in three European countries, Reichersdorfer et al (2013, pp.…”
Section: Social Accountability In Practice: Elements Of An Accountability Relationshipmentioning
confidence: 99%
“…The disappointing results have cast doubts on the effectiveness of the bottom-up accountability strategy for improving the delivery of public services, reducing corruption, and enhancing government efficiency. Some authors (Fox 2015;Ankamah 2019) have suggested that social accountability without "teeth," defined as the government's capacity to respond to citizens' voices, has limited impact.…”
Section: A Introductionmentioning
confidence: 99%